Nanofibrous hollow microspheres self-assembled from star-shaped polymers as injectable cell carriers for knee repair - Liu, Xiaohua (2011)
Biomaterials play pivotal roles in engineering tissue regeneration and repair. To regenerate irregular shaped defects, injectable cell carriers are desirable. Here, we report the development of self-assembled nanofibrous hollow microspheres from star-shaped biodegradable polymers as an injectable cell carrier for tissue regeneration. The nanofibrous hollow microspheres were shown to efficiently accommodate cells and enhance cartilage regeneration over control microspheres. The nanofibrous hollow microspheres also supported a significantly larger amount and higher quality cartilage regeneration over the chondrocytes alone group in an ectopic implantation model. In a critical-size rabbit osteochondral defect repair model, the nanofibrous hollow microspheres/chondrocytes group achieved substantially better cartilage repair and integration compared to the chondrocytes alone group that simulates the clinically available autologous chondrocyte implantation (ACI) procedure. These results indicate that the nanofibrous hollow microspheres are an excellent cell carrier for cartilage regeneration and are worthy of further investigation towards the aimed clinical application.